Inside man. year one [videorecording (DVD)] - Moffat, Steven, 1961-; Tennant, David, 1971-; West, Lydia (Actor); Wells, Dolly, 1971-; Tucci, Stanley (BBC, 2024)
Jefferson Grieff is on Death Row in an American prison for brutally murdering his wife. But it turns out that Grieff has a gift: he can solve crimes from inside his cell, and that is exactly why English journalist Beth Davenport needs his help. A woman who recently helped Beth has gone missing, with the only clue being a text with a blurry image of a man lunging towards the camera. Will Grieff crack the case in time? And is it possible to solve a crime before it has been committed?